2019
DOI: 10.1186/s12885-019-6055-9
|View full text |Cite
|
Sign up to set email alerts
|

First-degree family history of breast cancer is associated with prostate cancer risk: a systematic review and meta-analysis

Abstract: Background The relationship between first-degree family history of female breast cancer and prostate cancer risk in the general population remains unclear. We performed a meta-analysis to determine the association between first-degree family history of female breast cancer and prostate cancer risk. Methods Databases, including MEDLINE, Embase, and Web of Science, were searched for all associated studies that evaluated associations between first-degree family history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…The signi cance of our review was to provide suggestions on screening and early detection of second primary cancer after pelvic RT. Accumulated evidence showed that patients with cancer history increase the risk of second primary cancer (19), we suppose that radiotherapy would exacerbate this situation. We conducted a systematic review and meta-analysis to demonstrate the relationship between the exposure of pelvic radiation and developing secondary bladder cancer.…”
Section: Introductionmentioning
confidence: 93%
“…The signi cance of our review was to provide suggestions on screening and early detection of second primary cancer after pelvic RT. Accumulated evidence showed that patients with cancer history increase the risk of second primary cancer (19), we suppose that radiotherapy would exacerbate this situation. We conducted a systematic review and meta-analysis to demonstrate the relationship between the exposure of pelvic radiation and developing secondary bladder cancer.…”
Section: Introductionmentioning
confidence: 93%
“…It is well known that BRCA genes are considered as the principal biomarkers for the genetic study of hereditary breast and ovarian cancers [ 27 ]; however, several authors have also reported an association in patients affected with HPCa, which is part of HBOC syndrome [ 8 , 15 , 28 ]. BRCA1 and BRCA2 are tumor suppressor genes, localized on chromosomes 17 and 13, respectively, involved in repairing DNA double strand breaks by the conservative approach of homologous recombination (HR) [ 29 ].…”
Section: Genes Involved In the Predisposition To Hereditary Prostamentioning
confidence: 99%
“…BRCA1 and BRCA2 are tumor suppressor genes, localized on chromosomes 17 and 13, respectively, involved in repairing DNA double strand breaks by the conservative approach of homologous recombination (HR) [ 29 ]. The germline BRCA1 mutations increase the risk of HPCa by 3.8-fold in men aged <65 years, and germline BRCA2 mutations by 8.6-fold [ 8 ]. In a study performed on a cohort of 2019 HPCa patients, 0.9% germline mutations in BRCA1 and 3% in BRCA2 were observed [ 30 ].…”
Section: Genes Involved In the Predisposition To Hereditary Prostamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests a link between prostate cancer and BRCA2 gene mutations, with an increased relative risk of between 2.5–8.6 and more aggressive disease observed in mutation carriers 10 . BRCA genes are the most well‐known genes linked to breast cancer risk; a recent systematic review has suggested that having a first‐degree female relative with breast cancer may increase an individual's risk of prostate cancer by 18% 11 . As such, it is imperative to ask about family history during any consultation with men wishing to know their risk of having a significant prostate cancer.…”
Section: Risk Factors For Prostate Cancermentioning
confidence: 99%